Alterations of Oxidative Stress Indicators, Antioxidant Enzymes, Soluble Sugars, and Amino Acids in Mustard [Brassica juncea (L.) Czern and Coss.] in Response to Varying Sowing Time, and Field Temperature - Chauhan, Jyoti; Srivastava, J. P.; Singhal, Rajesh Kumar; Soufan, Walid; Dadarwal, Basant Kumar; Mishra, Udit Nandan; Anuragi, Hirdayesh; Rahman, Md Atikur; Sakran, Mohamed I.; Brestic, Marian; Zivcak, Marek; Skalicky, Milan; et al. (Frontiers in Plant Science, 2022)
Elevated temperature during reproductive stage is becoming one of crucial abiotic stresses influencing growth and production of several crop species, including Indian mustard . This study aimed to reveal how sowing time and changing temperature influence on regulation of oxidative stress indicators, antioxidant enzymes activity, accumulation of soluble sugars, and amino acids . The current study was carried out during the rabi 2017-18 and 2018-19 where five varieties of mustard viz. Pusa Mustard 25 (PM-25) (V1), PM-26 (V2), BPR-541-4 (V3), RH- 406 (V4), and Urvashi (V5) were grown under the field conditions on October 30 (normal sowing; S1), November 18 (late sowing; S2) and November 30 (very late sowing; S3) situations. Out of the three different sowing times, S1 and S3 leaves at mid flowering stage showed a significant variation in accumulation of soluble sugars (8.5 and 17.3%), free amino acids (235.4 and 224.6%), and proline (118.1 and 133%) contents, respectively during the rabi seasons 2017-18 and 2018-19, and plays a crucial role in osmotic adjustment. The results showed that very late sowing (S3) plants at mid flowering stage, exhibited a significant induction of the hydrogen peroxide (H2O2) (110.2 and 86.6%) and malondialdehyde (MDA) (23.5 and 47.5%) concentrations respectively, which indicated the sign of oxidative stress in plants. Interestingly, the polyphenol oxidase, peroxidase, superoxide dismutase, and catalase enzyme activity significantly increased in S3 (November 30) plants compared to S1, which played significant role in ameliorating the oxidative stress in plants. Furthermore, several fatty acid levels such as palmitic, stearic, oleic, and linoleic acids level significantly increased at S3 plants while the linolenic acid level decreased. The contents of eicosenoic acid increased and erucic acid content reduced, which affects the seed and oil quality in mustard. According to the results of this study it is clear that late sowing and changing temperature significantly impaired in the biochemical processes of Indian mustard plants. Furthermore comparison of varietal performances the V4 (RH-406) mustard would be effective for cultivation as well as environmental stress adoption in Indian soils, and it can be useful in breeding programs for developing heat-tolerant genotypes with ensuring food security.